Mothering, public leadership, and women's life writing : explorations in spirituality studies and practical theology - Wolfteich, Claire E. (Theology in Practice, 2017)
In Mothering, Public Leadership, and Women's Life Writing , Claire E. Wolfteich presents a series of case studies in Christian spirituality, bringing mothers' autobiographical writing into focus for theological reflection. From the medieval mystic Margery Kempe to the twentieth-century activist Dorothy Day, from African American preacher Jarena Lee to labor organizer Dolores Huerta, the book mines women's first-person writing, surfacing critical issues for theological analysis. Listening deeply to these diverse maternal voices, the book advances creative theological reflection on work, vocation, time poverty, Sabbath, and spiritual guidance. Mothering, Public Leadership, and Women's Life Writing demonstrates the significance of the study of mothering for theology and spirituality studies and the import of life writing as an underutilized source for practical theology.